L-Proline Catalyzed Synthesis of Novel 5-[2-(2-phenylpiperazin-1-yl)quinolin] methylene-2,4-dione Derivatives - Kumar Darsi, S.S. Praveen; Kumar, K. Shiva; Devi, B. Rama; Naidu, A.; Dubey, P.K. (Letters in Organic Chemistry, 2014)
L-proline is found to be an efficient catalyst for the Knoevenagel condensation of 2-chloroquinoline-3- carboxaldehyde 1a-c with an active methylene compound i.e., 2,4-thazolidinedione 2 in IPA affording novel substituted olefins 3a-c. The latter products reacted with N-substituted-3-phenylpiperazine 4a-c in the presence of KF in DMF to afford the corresponding 5-[2-(2-phenylpiperazin-1-yl)quinolin]methylene-2,4-dione derivatives 6a-i. Alternatively, 6ai were also synthesized from another reaction sequence 1 → 5 → 6. The structures of the synthesized compounds have been established on the basis of spectral and analytical data.
Keywords: Knoevenagel condensation